Strategies for the Use of Water Hyacinth (Eichhornia Crassipes) Towards the Production of Bioethanol - Monroy, Andres; Martínez Z, José J.; Caicedo Pineda, Gerardo Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The water hyacinth (Eichhornia crassipes) is considered an invasive species, due to the high adaptability to a wide type of aquatic ecosystems affects the natural balance causing the decreasing of oxygen, flora and fauna, and consequently the eradication in theses aquatic systems is harder. This biomass has a high concentration of cellulose and hemicellulose and a low lignin content which could be used as an energy resource. In this review, we revise the potential use of this aquatic plant, indicating the different types of processes that are carried out for its transformation into bioethanol production, indicating the aspects as the importance of this type of raw material, followed by the phases of pretreatment, hydrolysis, fermentation and distillation that it undergoes, until reaching the final product.